Molecular phylogeny and taxonomic revision of chaetophoralean algae (Chlorophyta) - Caisová, Lenka (Jihočeská univerzita, 2011)
Since the human inclination to estimate and trace natural diversity, usable species definitions as well as taxonomical systems are required. As a consequence, the first proposed classification schemes assigned the filamentous and parenchymatous taxa to the green algal order Chaetophorales sensu Wille. The introduction of ultrastructural and molecular methods provided novel insight into algal evolution and generated taxonomic revisions based on phylogenetic inference. However, until now, the number of molecular phylogenetic studies focusing on the Chaetophorales s.s. is surprisingly low. To enhance knowledge about phylogenetic relationships among taxa within the order, the nuclear?encoded SSU rDNA sequences from 30 strains covering all three chaetophoralean families have been investigated. All revealed monophyletic groupings were further screened for molecular non-homoplasious synapomorphies within the Viridiplantae. To address the question of the correspondence between morphological characters traditionally used for taxonomical delimitation of the Chaetophorales and the tree topology favored by molecular data, the list of morphological/ ultrastructural/ecological characters was elaborated and further analyzed. In addition, to obtain a close-up view into the evolution of Compensatory Base Changes (CBCs) of the second internal transcribed spacer (ITS2) which is currently often used to delimit putative biological species, 86 newly obtained/published sequences of ITS2 for five families of the order Ulvales were analyzed. Furthermore, a detailed comparative study of all ITS2 substitutions has been done. Subsequently all revealed CBCs and hemi- CBCs have been mapped upon the ITS2 phylogenetic tree topology. Finally, CBCs/hCBCs taxonomic inference in the Ulvales has been discussed.
Molecular phylogeny and taxonomic revision of chaetophoralean algae (Chlorophyta)
Keywords: Aphanochaete; Caespitella; CBC; CBC-clade; CBC-grade; Chaetophora; Chaetophorales; Chaetophoralean algae; Chlorophyceae; Fritschiella; evolution; hemi-CBC; ITS2; molecular; NHS; nuclear?encoded SSU rDNA; phenetic; phylogeny; polyphyly; Schizomeris; secondary structure; species concept; Stigeoclonium; Ulvales; Ulvophyceae; Uronema; Aphanochaete; Caespitella; CBC; CBC-clade; CBC-grade; Chaetophora; Chaetophorales; Chaetophoralean algae; Chlorophyceae; Fritschiella; evolution; hemi-CBC; ITS2; molecular; NHS; nuclear?encoded SSU rDNA; phenetic; phylogeny; polyphyly; Schizomeris; secondary structure; species concept; Stigeoclonium; Ulvales; Ulvophyceae; Uronema